2012
DOI: 10.14310/horm.2002.1376
|View full text |Cite
|
Sign up to set email alerts
|

Differences in plasma apelin and visfatin levels between patients with type 1 diabetes mellitus and healthy subjects and response after acute hyperglycemia and insulin administration

Abstract: OBJEcTIVE. Previous data suggest that apelin and visfatin play a role in metabolism and glucose homeostasis. The aim of the present study was to determine differences in plasma apelin and visfatin concentrations between healthy subjects and patients with type 1 diabetes mellitus and to study the effect of hyperglycemia and insulin administration on their levels in patients with type 1 diabetes mellitus. DEsIGN. One hundred patients with T1DM and 52 healthy subjects were examined. Nine patients with type 1 diab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
13
1
2

Year Published

2014
2014
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 40 publications
5
13
1
2
Order By: Relevance
“…Besides, Brendt et al [30] study showed that there is a significant relationship between visfatin concentrations and BMI and the percentage body fat in non-diabetic subjects. In disagreement with our study López-Bermejo et al [9]; Haider et al [6] and Alexiadous et al [15] stated no relationship between visfatin levels and BMI in type 1 diabetic subjects.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Besides, Brendt et al [30] study showed that there is a significant relationship between visfatin concentrations and BMI and the percentage body fat in non-diabetic subjects. In disagreement with our study López-Bermejo et al [9]; Haider et al [6] and Alexiadous et al [15] stated no relationship between visfatin levels and BMI in type 1 diabetic subjects.…”
Section: Discussioncontrasting
confidence: 99%
“…Similarly, Alexiadou et al [15] study on type 1 diabetic adult patients found that fasting visfatin levels tended to be lower in patients with type 1 diabetes in comparison to healthy subjects.…”
Section: Discussionmentioning
confidence: 90%
“…Few studies have evaluated the link between type 1 diabetes and serum apelin concentrations and the results are conflicting. Among the three studies published, two reported higher serum apelin levels in patients with type 1 diabetes than in controls . The first study compared 30 type 1 diabetic children with 45 controls and found no difference regarding age, BMI, gender, weight and lipid profile.…”
Section: Discussionmentioning
confidence: 99%
“…In type 1 diabetes, only three studies have assessed plasma apelin concentrations. Two studies reported higher circulating apelin levels in type 1 diabetic patients than in healthy controls: one study in children and one study in adult patients . In contrast, a recent study reported no difference in the circulating apelin levels between patients with type 1 diabetic patients and controls …”
Section: Introductionmentioning
confidence: 96%
“…Few studies have however reported the concentrations in type 1 diabetic patients and did the comparison with type 2 diabetic patients. In a first report, Alexiadou et al (2012) showed that fasting plasma apelin concentrations were higher in type 1 diabetic patients compared to healthy subjects. However, apelin levels in diabetic subjects were not modified during an oral glucose tolerance test suggesting that they were not affected by high blood glucose.…”
Section: Plasma Apelin Concentrations In Diabetesmentioning
confidence: 99%